A semiotic reading of “framing theories”: reinterpreting framing through the Peircean category of thirdness - Gradim, Anabela (2017)
This paper explores the semiotic character of framing theories, while suggesting new frameworks for the history of semiotics and its field. Frame studies, which are very fruitful in journalistic analysis and media criticism, have diverse sources. This work explores them, seeking to introduce a new strand to this genealogy, one that is particularly overlooked and relates to the work of semiotics as hermeneutical instrument for creating sense and meaning. Peirce’s category system is then presented as a method for exposing the underlying mechanisms of framing, found in their producers, in media texts and in the audience. Thirdness is envisaged as an element that creates rules or interpretative habitus, which will be identi ed with framing in narratives, and as an integrating paradigm that is able to overcome the fragmentation of the eld of frame studies and its origins. A semiotic reading of “framing theories”: reinterpreting framing through the Peircean category of thirdness